2006
DOI: 10.1038/sj.ejhg.5201732
|View full text |Cite
|
Sign up to set email alerts
|

Multiple QTL influence the serum Lp(a) concentration: a genome-wide linkage screen in the PROCARDIS study

Abstract: The serum concentration of lipoprotein Lp (a) is known to be highly heritable and associated with cardiovascular risk. A genome-wide variance component linkage analysis was performed to localise quantitative trait loci (QTLs) influencing Lp(a) levels in a large cohort collected in the PROCARDIS coronary heart disease study. Highly significant linkage was detected at the previously described LP(a) locus on chromosome 6q27 (LOD 108). Taking into account the effect of the locus detected on chromosome 6, a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…7,22,23 Several studies sought to identify genetic variation in LPA that explains variation in lipoprotein(a) levels and further define the association with CAD risk beyond the contribution of the well-established copy number variation in the KIV-2 domains. This resulted mainly in identification of SNPs that act as proxy markers of the KIV-2 CNV 5,24 or have no proven functional role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,22,23 Several studies sought to identify genetic variation in LPA that explains variation in lipoprotein(a) levels and further define the association with CAD risk beyond the contribution of the well-established copy number variation in the KIV-2 domains. This resulted mainly in identification of SNPs that act as proxy markers of the KIV-2 CNV 5,24 or have no proven functional role.…”
Section: Discussionmentioning
confidence: 99%
“…6 A large proportion of lipoprotein(a) level variation is inherited and is mainly attributed to genetic variation within the LPA gene that encodes apolipoprotein(a), the characteristic protein moiety of the particle. 7 Genetic variation in the LPA gene is defined by a repetitive genomic region harboring 2 exons encoding one of the kringle domains (kringle IV [KIV]-2) in apolipoprotein(a), resulting in a highly polymorphic protein that includes multiple copies of the kringle domain ranging in number from 3 to >40. 8 This variation has been proposed to directly affect circulating lipoprotein(a) levels by influencing the processing and secretion of apolipoprotein(a) isoforms from producing hepatocytes 9,10 The copy number of KIV-2 repeats is inversely related to levels with larger molecules, hindering efficient secretion and resulting in lower circulating lipoprotein(a) levels.…”
mentioning
confidence: 99%
“…As outlined below, populations differ in allele-associated Lp(a) concentrations. Hence, in populations where long alleles are associated with higher concentrations, e.g., Africans, more 13q22-31, 11p14-15, and 1q23 (129,130), but these have not been confirmed, either.…”
Section: Downloaded Frommentioning
confidence: 92%
“…They found that the rs10455872 and rs3798220 SNPs in the LPA gene explained 25% and 8% of the variation in plasma Lp(a) concentrations, and each was associated with high risk of coronary heart disease. Importantly, in numerous other studies, including genome-wide linkage and association studies, multiple genetic variants in or around LPA on chromosome 6q27 were also found to be major determinants of plasma Lp(a) concentrations (39, [89][90][91][92][93]. For Mendelian residence time, e.g., enhanced binding of Lp(a) selectively to the matrix in the intima.…”
Section: Lp(a) In Normal Atherosclerotic and Injured Intimamentioning
confidence: 95%